The Application of Alkynes as 1,2-Dicarbonyl Substitutes in Organic Synthesis Through Iodination and Kornblum Oxidation - Acharya, Swadhin Swaraj; Rout, Padma Ranjan; Parida, Bibhuti Bhusan (Synlett, 2025)
The 1,2-dicarbonyls are excellent moieties in organic synthesis and they offer scopes for the synthesis of numerous interesting heterocycles. Likewise, the alkynes are widespread in nature and drugs. Herein, this article highlights the application of alkynes in organic synthesis as 1,2-dicarbonyl surrogates by I2/DMSO and NIS/DMSO-mediated oxidations through a cascade of iodination and Kornblum oxidation. These approaches are mild, efficient, and tolerate many functional groups. The NIS/DMSO and iodine–DMSO-mediated oxidation of alkynes to 1,2-dicarbonyl compounds and trapping by several nucleophiles to construct important diversely functionalized heterocycles have been discussed in this article. The state of the art, challenges, and future perspective have been highlighted in the present collection.
Keywords: Kornblum oxidation; I2–DMSO; NIS–DMSO; Alkyne; 1,2-Dicarbonyl